Rosuvastatin vs. protease inhibitor switching for hypercholesterolaemia: a randomized trial. Issue 8 (14th March 2016) - Lee, FJ; Monteiro, P; Baker, D; Bloch, M; Roth, N; Finlayson, R; Moore, R; Hoy, J; Martinez, E; Carr, A
Abstract : Objectives: The aim of the study was to compare the efficacy and safety of rosuvastatin initiation with those of switching of ritonavir‐boosted protease inhibitors (PI/rs) in HIV‐1‐infected adults with hypercholesterolaemia and increased cardiovascular risk scores. Methods: In this open‐label, multicentre study, HIV‐1‐infected adults on PI/r‐based therapy with viral load < 50 HIV‐1 RNA copies/mL, fasting total cholesterol ≥ 5.5 mmol/L (both for ≥ 6 months) and elevated cardiovascular risk (Framingham score ≥ 8% or diabetes or family history), and not on lipid‐lowering therapy, were randomized to open‐label rosuvastatin 10 mg/day or to PI/r switching, both with standardized diet/exercise advice. The primary endpoint was change in total cholesterol at week 12 (intention to treat). Results: There were 43 participants (23 on rosuvastatin). Baseline characteristics were: mean [± standard deviation (SD)] age 55 (8.5) years, 42 (98%) male, 41 (95%) white race, and mean (± SD) total cholesterol 6.2 (1.2) mmol/L. At enrolment, PI/rs were lopinavir/ritonavir ( n = 22; 51%), atazanavir/ritonavir ( n = 12; 28%) and darunavir/ritonavir ( n = 9; 21%). The commonest PI/r substitutes were raltegravir ( n = 9; 45%) and rilpivirine ( n = 4; 20%). All participants were adherent through to week 12. Rosuvastatin yielded greater declines than PI/r switching in total (− 21.4% vs . − 8.7%, respectively; P = 0.003) and low‐density lipoprotein (− 29.9% vs . − 1.0%, respectively; P < 0.001) cholesterol, but smaller declines in very low‐density lipoprotein cholesterol and triglycerides ( P < 0.01). Cholesterol lowering was greater in participants on atazanavir/ritonavir or once‐daily darunavir/ritonavir ( vs . lopinavir/ritonavir). More study drug‐related adverse events (mostly grade 1 nausea/diarrhoea; 10 vs . one, respectively; P = 0.001) occurred with PI/r switching than with rosuvastatin. Conclusions: In adults receiving a PI/r, rosuvastatin 10 mg/day for 12 weeks yielded larger decreases in total and low‐density lipoprotein cholesterol than PI/r switching, and was better tolerated.